Improved control over spontaneously formed GaN nanowires in molecular beam epitaxy using a two-step growth process. (12th October 2015) - Zettler, J K; Corfdir, P; Geelhaar, L; Riechert, H; Brandt, O; Fernández-Garrido, S
Abstract: We investigate the influence of modified growth conditions during the spontaneous formation of GaN nanowires (NWs) on Si(111) in plasma-assisted molecular beam epitaxy. We find that a two-step growth approach, where the substrate temperature is increased during the nucleation stage, is an efficient method to gain control over the area coverage, average diameter, and coalescence degree of GaN NW ensembles. Furthermore, we also demonstrate that the growth conditions employed during the incubation time that precedes nanowire nucleation do not influence the properties of the final nanowire ensemble. Therefore, when growing GaN NWs at elevated temperatures or with low Ga/N ratios, the total growth time can be reduced significantly by using more favorable growth conditions for nanowire nucleation during the incubation time.